1979
DOI: 10.2118/7053-pa
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Phase Behavior and Retention in Porous Media

Abstract: Glover, C.J.,* SPE-AIME, Exxon Production Research Puerto, M.C., SPE-AIME, Puerto, M.C., SPE-AIME, Exxon Production Research Co. Maerker, J.M., SPE-AIME, Exxon Production Research Co. Sandvik, E.L., SPE-AIME, Exxon Production Research Co. Abstract Surfactant retention in reservoir rock is a major factor limiting effectiveness of oil recovery using microemulsion flooding processes. Effects of salinity and surfactant concentration on microemulsion phase behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 0 publications
9
78
0
Order By: Relevance
“…Healy and Reed (1977) Nonyl surfactant (anionic) It was reported that ultralow interfacial tension between microemulsion-oil systems increases the oil recovery efficiency 4. Glover et al (1979) Monoethanol amine salt of dodecylorthoxylene sulfonic acid (anionic)…”
Section: Chemical Thermalmentioning
confidence: 99%
See 1 more Smart Citation
“…Healy and Reed (1977) Nonyl surfactant (anionic) It was reported that ultralow interfacial tension between microemulsion-oil systems increases the oil recovery efficiency 4. Glover et al (1979) Monoethanol amine salt of dodecylorthoxylene sulfonic acid (anionic)…”
Section: Chemical Thermalmentioning
confidence: 99%
“…For good efficiency of microemulsions and reasonable oil recovery efficiency, the surfactant must be chemically stable, reduce the interfacial tension between brine and crude oil and displace the oil without significant surfactant loss by adsorption on the reservoir rocks. Retention of surfactant is a most restrictive factor that affects the efficiency of the oil recovery process by microemulsion flooding (Glover et al 1979). The microemulsion slug partitions into three phases such as a surfactant-rich middle-phase and surfactant-lean brine and oil phases Reed 1974, 1977;Healy et al 1976) in the intermediate salinity range.…”
Section: Surfactant/microemulsion Floodingmentioning
confidence: 99%
“…These factors include the surfactant types (Hayes et al, 1979), chemistry (Enedy et al, 1982;Hirasaki et al, 1983;Krumrine et al, 1982), phase behavior (Glover et al, 1979;Novosad, 1982), chemicals adsorption (Austad et al, 1997), surfactant precipitation and redissolution (Somasundaran et al, 1984), chromatographic separation of chemicals (Li et al, 2009), surfactant convection (Ramirez et al, 1980), surfactant stability (Handy et al, 1982), chemicals loss (Friedmann, 1986), dispersion (Hirasaki, 1981), surfactant systems formulation (Salager et al, 1979), wettability , reservoir rock structure and morphology (Dullien et al, 1972;Yadali Jamaloei and Kharrat, 2009;Yadali Jamaloei et al, 2011a), and reservoir heterogeneity (Ma et al, 2007). The morphology and heterogeneity of the reservoir rock play a significant role in the behavior of chemical flooding processes.…”
Section: Factors That Influence the Chemical Floodingmentioning
confidence: 99%
“…Adsorption of surfactants considered for EOR applications has been studied extensively. [16][17][18][19][20][21] Surfactant retention was evaluated by comparing the adsorption isotherm of surfactin with that of the benchmark chemical surfactant.…”
Section: Introductionmentioning
confidence: 99%